1992
DOI: 10.1007/bf01308078
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and gastrointestinal effects of nabumetone or its active metabolite, 6-methoxy-2-naphthylacetic acid (6MNA)

Abstract: 6MNA, the active metabolite of the nonacidic antiinflammatory drug nabumetone, was investigated using intravenous administration for effects on (1) carrageenan paw edema and gastric irritancy compared with either oral nabumetone or both oral and intravenous indomethacin when given acutely and (2) gastrointestinal irritancy when given in repeat dosing studies. Oral doses of nabumetone or intravenous 6MNA produced effective antiinflammatory activity together with significant inhibition of paw exudate PGE2. Antii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In respect of (i) our studies show that parenteral indomethacin uncouples intestinal mitochondrial oxidative phosphorylation or inhibits electron transport via excretion in bile. Indeed most NSAIDs, apart from the active metabolite of nabumetone, 6-MNA, and aspirin have a significant biliary excretion component27 49 which exposes both the stomach (reflux of duodenal contents) and the small intestine to concentrations of the drug which may be sufficiently high to uncouple, depending on the doses given. We could not demonstrate small intestinal toxicity following very large doses of nabumetone or an effect to uncouple oxidative phosphorylation in vivo or in vitro which accords with its purported favourable gastrointestinal side effect profile in humans 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In respect of (i) our studies show that parenteral indomethacin uncouples intestinal mitochondrial oxidative phosphorylation or inhibits electron transport via excretion in bile. Indeed most NSAIDs, apart from the active metabolite of nabumetone, 6-MNA, and aspirin have a significant biliary excretion component27 49 which exposes both the stomach (reflux of duodenal contents) and the small intestine to concentrations of the drug which may be sufficiently high to uncouple, depending on the doses given. We could not demonstrate small intestinal toxicity following very large doses of nabumetone or an effect to uncouple oxidative phosphorylation in vivo or in vitro which accords with its purported favourable gastrointestinal side effect profile in humans 2…”
Section: Discussionmentioning
confidence: 99%
“…Of the NSAIDs studied in the rat, aspirin by gavage (and intraperitoneally)8 is the only conventional NSAID, apart from nabumetone,27 that does not cause small intestinal ulcers. Aspirin and nabumetone (6-MNA) are also not excreted in significant amounts in bile following parenteral administration 28.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its inability to dissociate and its very low solubility in aqueous media, nabumetone is practically not absorbed from the stomach, therefore it does not affect prostanoid production in the stomach locally [5]. Following absorption in the small intestine, nabumetone is rapidly converted by the liver to its active metabolite, 6-MNA, which is a relatively selective COX-2 inhibitor and has more potent anti-inflammatory and analgesic properties [20,21]. In contrast to nabumetone, it was demonstrated that 6-MNA inhibited the synthesis of gastroprotective prostanoids in vitro [5].…”
Section: Discussionmentioning
confidence: 99%
“…Postmarketing surveys have Ülker/Önal/Hatip/Sürücü/Alkanat/Koşay/ Evinç been used to support claims that new NSAI drugs, nabumetone and etodolac, have few gastric or renal side effects [17]. These NSAI drugs do not inhibit COX-1 prostaglandins which occur in the stomach and kidneys, but more selectively block COX-2 prostaglandins, which cause arthritic inflammation [17][18][19][20]. As an inhibitor of COX-2, nabumetone removes the prostaglandins having proinflammatory effects and mediating the vascular events of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs capability to interact with COX-1 and COX-2 is directly related to its chemical properties allowing the carboxylic acid the interaction with COX-1 and having lipophilic drugs a more strong interaction with COX-2 [35]. So, non-selective COX inhibitors generally have carboxylic acids or ketoenolic acids in their constitution while COX-2 selective inhibitors have sulphonamide functional groups on a diarylheterocyclic ring.…”
Section: Chemical Classificationmentioning
confidence: 99%